2020
DOI: 10.1038/s41598-020-62166-w
|View full text |Cite
|
Sign up to set email alerts
|

Advanced gelatin-based vascularization bioinks for extrusion-based bioprinting of vascularized bone equivalents

Abstract: Bone tissue is highly vascularized. the crosstalk of vascular and osteogenic cells is not only responsible for the formation of the strongly divergent tissue types but also for their physiological maintenance and repair. extrusion-based bioprinting presents a promising fabrication method for bone replacement. It allows for the production of large-volume constructs, which can be tailored to individual tissue defect geometries. In this study, we used the all-gelatin-based toolbox of methacryl-modified gelatin (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 58 publications
0
79
0
Order By: Relevance
“…Gelatin alone is usually used as a sacrificial material that liquifies at 37 °C, but GelMA is a stronger material crosslinked irreversibly by UV. [119] Within MPSs, it may be a promising material for lymphangiogenesis-or angiogenesis-based vascularization methods, but encapsulating ECs within the material would require careful tuning of UV dosage to ensure that the encapsulated cells can still perform vasculogenesis following exposure. Interestingly, many reports detail the tuning of Gel-MA's stiffness via addition of other polymers [120,121] or adjustment of the material handling, [122][123][124] which shows potential translation to tissue-specific MPSs such as vascularized bone or tumor models, or soft-tissue MPSs replicating fat, lymphatic, or nerve tissues.…”
Section: Other Hydrogel Materials In Vascularized Mpss: a Brief Perspmentioning
confidence: 99%
“…Gelatin alone is usually used as a sacrificial material that liquifies at 37 °C, but GelMA is a stronger material crosslinked irreversibly by UV. [119] Within MPSs, it may be a promising material for lymphangiogenesis-or angiogenesis-based vascularization methods, but encapsulating ECs within the material would require careful tuning of UV dosage to ensure that the encapsulated cells can still perform vasculogenesis following exposure. Interestingly, many reports detail the tuning of Gel-MA's stiffness via addition of other polymers [120,121] or adjustment of the material handling, [122][123][124] which shows potential translation to tissue-specific MPSs such as vascularized bone or tumor models, or soft-tissue MPSs replicating fat, lymphatic, or nerve tissues.…”
Section: Other Hydrogel Materials In Vascularized Mpss: a Brief Perspmentioning
confidence: 99%
“…Takei et al have shown that the bFGF releasing PLA‐gelatin scaffold results in significant enhancement of angiogenesis and further remarkable hepatocyte survival in comparison with bFGF‐free scaffolds. In this study, bFGFcontaining scaffolds showed no adverse effect on engrafted hepatocytes because the glycogen storage of cells remained unchanged (Leucht, Volz, Rogal, Borchers, & Kluger, 2020).…”
Section: Signaling Moleculesmentioning
confidence: 78%
“…Banfi et al (2012), Chiu and Radisic (2010), Kant and Coulombe (2018), Langenfeld and Langenfeld (2004), Leucht et al (2020), Lovett et al (2009), Milkiewicz et al (2006), Rouwkema and Khademhosseini (2016), Rouwkema et al (2008), Saik et al (2011), Salybekov et al (2018), Vijayan et al (2019), and…”
Section: Signaling Moleculesmentioning
confidence: 99%
“…The addition of other component of the ECM such as fibronectin, collagens, or glycosaminoglycans in the hydrogels could enable the production of even more biomimetic platforms. Moreover, gelatin has shown its potential in the creation of vascularized tissues through bioprinting technologies [ 229 ] that might help in the production of vascularized tumors. Also, in the last years new efforts have been made to study the role of the immune system in the tumor progression.…”
Section: Engineering the Tme Using Protein‐based Hydrogelsmentioning
confidence: 99%